Use of adhesively inserted full-ceramic restorations in the conservative treatment of amelogenesis imperfecta: a case report - (:unkn) unknown (My University, 2003)
Amelogenesis imperfecta is an inherited disorder that presents a major challenge to the dentist for prosthetic treatment of missing and/or malformed tooth structures. This clinical report presents the use and short-term clinical performance of adhesively-inserted full-ceramic restorations in the restoration of a case of amelogenesis imperfecta.
Keywords: Female; Humans; Adolescent; Follow-Up Studies; Crowns; Dental Prosthesis Design; Dental Veneers; Dental Bonding; Tooth Preparation; Amelogenesis Imperfecta; Ceramics